Gas sensing performance of In2O3 nanostructures: A mini review - Yang, Shulin; Yin, Huan; Wang, Zhao; Lei, Gui; Xu, Huoxi; Lan, Zhigao; Gu, Haoshuang (Frontiers in Chemistry, 2023)
Effective detection of toxic and hazardous gases is crucial for ensuring human safety, and high-performance metal oxide-based gas sensors play an important role in achieving this goal. In2O3 is a widely used n-type metal oxide in gas sensors, and various In2O3 nanostructures have been synthesized for detecting small gas molecules. In this review, we provide a brief summary of current research on In2O3-based gas sensors. We discuss methods for synthesizing In2O3 nanostructures with various morphologies, and mainly review the sensing behaviors of these structures in order to better understand their potential in gas sensors. Additionally, the sensing mechanism of In2O3 nanostructures is discussed. Our review further indicates that In2O3-based nanomaterials hold great promise for assembling high-performance gas sensors.